Checklist of Macroalgae at Krakal and Drini Beach, Gunungkidul - Suryandari, Retno (Proceeding International Conference on Science and Engineering, 2017)
Macroalgae are multicellular plants that do not produce seeds or flowers. All macroalgae are multicellular and do not have a specialized body structure and do not have reproductive mechanism like terrestrial plants. Macroalgae is divided into 3 groups namely Chlorophyta (green algae), Rhodophyta (red algae), and Phaeophyceae (brown algae). Green algae and red algae belong to the Plantae kingdom with green algae (Chlorophyta) and included in the Subkingdom Viridiplantae and red algae (Rhodophyta) into the Biliphyta subkingdom. Brown algae (Phaeophyta) belong to the Chromista kingdom. Based on the research, macroalgae found in Drini and Krakal Gunungkidul are green algae, red algae and brown algae. Green algae found and identified are Anadyomene plicata C. Agardh, Chaetomorpha antennina (Bory) K?tzing, Chaetomorpha linum (O.F. M?ller) K?tzing, Boergesenia forbesii (Hardvey) Feldmann, Cladophoropsis herpestica (Montagne) M. Howe, Boodlea composita (Harvey) F. Brand, Caulerpa peltata J.V. Lamoroux, Enteromorpha intestinalis (Linnaeus) Nees, Ulva lactuca Linnaeus. Red algae species found and successfully identified are Acrocystis nana Zanardini, Acanthophora spicifera (M. Vahl) Børgesen, Laurencia papilosa (C. Agardh) Greville, Actinotrichia fragilis (Forsskål) Børgesen, Galaxaura rugosa (J. Ellis & Solander) J.V. Lamoroux, Amphiora anceps (Lamark) Decaisne, Gelidiela acerosa (Forsskål) Feldmann & Hamel, Gracilaria canaliculata Sonder, Gelidiopsis intricata (C.Agardh) Vickers. Brown algae species found and identified are Lobophora variegata (J.V.Lamouroux) Womersley ex E.C.Oliveira, Padina minor Yamada, Sargassum crassifolium J. Agardh, Turbinaria ornata (Turner) J. Agardh. The species that classified as a new record in Indonesia are Cladophoropsis herpestica (Montagne) M. Howe and Gracilaria spinulosa (Okamura) Chang & B.M.Xia.